The Missing Globalization Puzzle - Bhavnani, Rikhil (IMF Working Papers; Working Paper ;, 2002)
The failure of declining trade-related costs to be reflected in estimates of the standard gravity model of bilateral trade might be called the "missing globalization puzzle." This puzzle is most apparent in the estimated distance coefficients found in the literature, which show no evidence of declining in absolute value over time. In contrast, we find evidence of globalization, on both cross-section and panel data, reflected in a variety of measures of geography. Our estimation procedure is consistent with recent theoretical developments that emphasize the importance of relative costs for determining bilateral trade patterns. But the main reason our findings differ from previous studies is our nonlinear specification, which has a number of advantages over the standard log-linear specification.